Collective Trauma and Mental Health in Adolescents: A Retrospective Cohort Study of the Effects of Retraumatization - Pazderka, Hannah; Brown, Matthew R. G.; Agyapong, Vincent I. O.; Greenshaw, Andrew James; McDonald-Harker, Caroline Beth; Noble, Shannon; Mankowski, Monica; Lee, Bonnie; Drolet, Julie L.; Omeje, Joy; Brett-MacLean, Pamela; Kitching, Deborah Terry; et al. (Frontiers in Psychiatry, 2021)
In the wake of the massive Canadian wildfire of May 2016 in the area of Fort McMurray Alberta, we observed increased rates of mental health problems, particularly post-traumatic stress disorder (PTSD), in school-aged adolescents (ages 11-19). Surprisingly, we did not see these rates decline over the 3.5-year follow-up period (Brown et al., in press). Additionally, our research suggested that the impact of this mass incident resulted in other unanticipated effects, including the finding that children who were not present for and relatively unaffected by the wildfire showed a similar PTSD symptom profile to children more directly involved, suggesting some degree of spillover or stress contagion. A potential explanation for these high rates in individuals who were not present could be undiagnosed retraumatization in some of the students. To investigate this possibility, we compared two groups of students: those who reported the wildfire as their most significant trauma (n=740) and those who had their most significant trauma prior to the wildfire (n=295). Those with significant pre-existing trauma had significantly higher rates of both depression and PTSD symptoms, although unexpectedly the groups exhibited no differences in anxiety level. Taken together, this evidence suggests retraumatization is both longer-lasting and more widespread than might be predicted on a case-by-case basis, suggesting the need to reconceptualize the role of past trauma history in present symptomatology. These findings point to the need to recognize that crises instigated by natural disasters are mass phenomena which expose those involved to numerous unanticipated risks. New trauma-informed treatment approaches are required that incorporate sensitivity to the collective impact of mass crises, and recognize the risk of poorer long-term mental health outcomes for those who experienced trauma in the past.